Antiretroviral therapy and early mortality in South Africa - Andrew Boulle; Peter Bock; Meg Osler; Karen Cohen; Liezl Channing; Katherine Hilderbrand; Eula Mothibi; Virginia Zweigenthal; Neviline Slingers; Keith Cloete; Fareed Abdullah
OBJECTIVE: To describe province-wide outcomes and temporal trends of the Western Cape Province antiretroviral treatment (ART) programme 5 years since inception, and to demonstrate the utility of the WHO monitoring system for ART. METHODS: The treatment programme started in 2001 through innovator sites. Rapid scaling-up of ART provision began early in 2004, located predominantly in primary-care facilities. Data on patients starting ART were prospectively captured into facility-based registers, from which monthly cross-sectional activity and quarterly cohort reports were aggregated. Retention in care, mortality, loss to follow-up and laboratory outcomes were calculated at 6-monthly durations on ART. FINDINGS: By the end of March 2006, 16 234 patients were in care. The cohort analysis included 12 587 adults and 1709 children. Women accounted for 70% of adults enrolled. After 4 and 3 years on ART respectively, 72.0% of adults (95% confidence interval, CI: 68.0-75.6) and 81.5% (95% CI: 75.7-86.1) of children remained in care. The percentage of adults starting ART with CD4 counts less than50 cells/µl fell from 51.3% in 2001 to 21.5% in 2005, while mortality at 6 months fell from 12.7% to 6.6%, offset in part by an increase in loss to follow-up (reaching 4.7% at 6 months in 2005). Over 85% of adults tested had viral loads below 400 copies/ml at 6-monthly durations until 4 years on ART. CONCLUSION: The location of care in primary-care sites in this programme was associated with good retention in care, while the scaling-up of ART provision was associated with reduced early mortality.